2018
DOI: 10.1016/j.exppara.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of normal human serum on the mouse trypanosome Trypanosoma musculi in vitro and in vivo

Abstract: Trypanosoma musculi, a common blood flagellate found in mice, is similar in morphology and life cycle to the rat trypanosome T. lewisi. Both species belong to the subgenus Herpetosoma, and as T. lewisi has recently been shown to be a zoonotic pathogen, there is concern that T. musculi could also be potentially infective to humans. To test this hypothesis, a well-established method, the normal human serum (NHS) incubation test, was carried out which distinguishes human and non-human infective trypanosomes. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…However, they do significantly differ in many aspects. In particular, T. lewisi infects only rats and sometimes humans (Sarataphan et al ., 2007; Verma et al ., 2011), while T. musculi infects only mice and is unlikely to be pathogenic to humans (Zhang et al ., 2018). A few research studies have indicated that both T. musculi and T. lewisi can modulate the host immune response in coinfections with various other infectious agents, to potentially cause more harm to the hosts, by altering the infection kinetics and increasing the duration of colonization in the host (Lowry et al ., 2014; Vaux et al ., 2016; Nzoumbou-Boko et al ., 2017; Gao et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, they do significantly differ in many aspects. In particular, T. lewisi infects only rats and sometimes humans (Sarataphan et al ., 2007; Verma et al ., 2011), while T. musculi infects only mice and is unlikely to be pathogenic to humans (Zhang et al ., 2018). A few research studies have indicated that both T. musculi and T. lewisi can modulate the host immune response in coinfections with various other infectious agents, to potentially cause more harm to the hosts, by altering the infection kinetics and increasing the duration of colonization in the host (Lowry et al ., 2014; Vaux et al ., 2016; Nzoumbou-Boko et al ., 2017; Gao et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%